Penentuan Pemilihan Lokasi Usaha Terbaik Menggunakan Metode AHP dan TOPSIS - Chairina, Bella; Mesra, Trisna; Belen, Maria; Alfian, Wahyu; Simanjuntak, Frans Risky; Pratama, Rizky (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Selecting a business location is a important strategic decision for UMKM, often hindered by subjectivity. This research aims to determine the best business location in Dumai City for UMKM owners. The methodology integrates the Analytic Hierarchy Process (AHP) for criteria weighting and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for alternative ranking. Data were collected from 20 respondents via questionnaires and interviews. Evaluation criteria included rental cost, accessibility, number of competitors, and location crowdedness . AHP results identified